2015
DOI: 10.1186/s12933-014-0165-0
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of peroxisome proliferator-activated receptors in cardiac and vascular remodeling in a novel minipig model of insulin resistance and atherosclerosis induced by consumption of a high-fat/cholesterol diet

Abstract: BackgroundA long-term high-fat/cholesterol (HFC) diet leads to insulin resistance (IR), which is associated with inflammation, atherosclerosis (AS), cardiac sympathovagal imbalance, and cardiac dysfunction. Peroxisome proliferator-activated receptors (PPARs) and nuclear factor ĸB (NF-κB) are involved in the development of IR-AS. Thus, we elucidated the pathological molecular mechanism of IR-AS by feeding an HFC diet to Tibetan minipigs to induce IR and AS.MethodsMale Tibetan minipigs were fed either a normal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…After 4 weeks of environmental accommodation, the animals were divided into a normal control (NC) group and an atherosclerosis model group with 5 animals per group. The atherosclerosis model was established by feeding minipigs with a high-fat/cholesterol (HFC) diet (containing 15% shortening oil, 1.5% cholesterol, 10% egg yolk powder, and 73.5% basal feed) for 24 weeks, as we previously described [9]. Minipigs were euthanized at the 24th week.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…After 4 weeks of environmental accommodation, the animals were divided into a normal control (NC) group and an atherosclerosis model group with 5 animals per group. The atherosclerosis model was established by feeding minipigs with a high-fat/cholesterol (HFC) diet (containing 15% shortening oil, 1.5% cholesterol, 10% egg yolk powder, and 73.5% basal feed) for 24 weeks, as we previously described [9]. Minipigs were euthanized at the 24th week.…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…Furthermore, the omnivorous nature of pigs makes them highly suitable for studying dietarybased patterns and for translating findings from pigs to humans [5]. In particular, Tibetan minipigs have many advantages as a model for studying diet-related cardiovascular metabolic diseases [9,10]. Our previous studies have shown that Tibetan minipigs are a viable model for studying atherosclerosis induced by dietary patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, peripheral fat accumulation is associated with macrophage infiltration into adipose tissue, which promotes the release of proinflammatory cytokines including tumour necrosis factor alpha (TNFα) (Wellen and Hotamisligil 2005). In a recent study, significantly higher levels of inflammatory markers, including TNFα, were found in the cardiac tissue of Tibetan mini pigs as a result of being fed a HF diet for 24 weeks (Yongming, Zhaowei et al 2015). Furthermore, rats fed a HF diet for 10 weeks demonstrated increased TNFα levels in the cortex of their kidneys (Elmarakby and Imig 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Impaired lipid metabolism and the ectopic deposition of fat have been found involved in the long‐term programming of diseases and related to the generation of a proinflammatory environment . Peroxisome proliferator activated receptor α (PPARα) is a ligand‐activated transcription factor with key functions in the regulation of lipid metabolism, antioxidant and antiinflammatory pathways, highly relevant in cardiac energy metabolism, cardiovascular remodeling, and vascular homeostasis . PPARα is one of the three identified PPARs, nuclear receptors that are activated by endogenous ligands of lipid nature, including diverse unsaturated fatty acids .…”
Section: Introductionmentioning
confidence: 99%